Pedagogy and practice in heritage studies - Bender, Susan J.; Messenger, Phyllis Mauch, 1950-; Shackel, Paul A. (Cultural heritage studies., 2019)
This volume challenges professors of anthropology (both practicing and aspiring) to incorporate pedagogies of engaged, critical learning into their classrooms. By showing how we can teach archaeology such that students realize that there are connections between our understandings of the past and the present, and that archaeological methods can illuminate the values of contemporary people, the case studies in this book create a framework for connecting archaeology curricula to heritage study.